Understanding the structure and function of Bacillus thuringiensis toxins. (January 2016) - Palma, Leopoldo; Berry, Colin
Abstract: As biological control agents take an expanding share of the pesticides market and the production of insect-resistant crops increases, it is essential to understand the structure and function of the active agents, the invertebrate-active toxins that are the fundamental ingredients of these control systems. The potential for these agents in industry, agriculture and medicine necessitates a thorough investigation of their activity. Highlights: Bacillus thuringiensis is the most used biological pesticide worldwide. This bacterium synthesises a number of invertebrate active toxins with specific activity. For several toxins, the mode of action remains still unknown. Determining their toxin structures will help to the elucidation of their mode of action. Understanding their mode of action will revolutionise our ability to exploit these toxins.